2017
DOI: 10.1155/2017/4313561
|View full text |Cite
|
Sign up to set email alerts
|

Chiglitazar Preferentially Regulates Gene Expression via Configuration-Restricted Binding and Phosphorylation Inhibition of PPARγ

Abstract: Type 2 diabetes mellitus is often treated with insulin-sensitizing drugs called thiazolidinediones (TZD), which improve insulin resistance and glycemic control. Despite their effectiveness in treating diabetes, these drugs provide little protection from eminent cardiovascular disease associated with diabetes. Here we demonstrate how chiglitazar, a configuration-restricted non-TZD peroxisome proliferator-activated receptor (PPAR) pan agonist with moderate transcription activity, preferentially regulates ANGPTL4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…Regarding PPAR‐δ, as yet there has been no drug approved in clinical practice, although animal experiments indicated that PPAR‐δ could raise the HDL‐C level without influencing the levels of TG, very‐low‐density lipoprotein, or low‐density lipoprotein cholesterol, and it might be involved in inhibition of inflammation . According to their mutually compensatory and sometimes antagonistic effects, a less potent and well‐balanced agonist targeting all 3 PPAR types may provide more comprehensive efficacy in T2DM treatment, which is to increase insulin sensitivity, regulate blood glucose, and minimize the side effects of metabolic dysfunction, cardiovascular disease, weight gain, and bone fracture, building up a brand‐new T2DM therapy …”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding PPAR‐δ, as yet there has been no drug approved in clinical practice, although animal experiments indicated that PPAR‐δ could raise the HDL‐C level without influencing the levels of TG, very‐low‐density lipoprotein, or low‐density lipoprotein cholesterol, and it might be involved in inhibition of inflammation . According to their mutually compensatory and sometimes antagonistic effects, a less potent and well‐balanced agonist targeting all 3 PPAR types may provide more comprehensive efficacy in T2DM treatment, which is to increase insulin sensitivity, regulate blood glucose, and minimize the side effects of metabolic dysfunction, cardiovascular disease, weight gain, and bone fracture, building up a brand‐new T2DM therapy …”
mentioning
confidence: 99%
“…Chiglitazar (CHI), a novel configuration‐restricted non‐TZD PPAR pan‐agonist, is currently in its phase 3 clinical development for treatment of patients with T2DM in China (http://www.chinadrugtrials.org.cn/, with registration number CTR20131996; https://clinicaltrials.gov, with registration identifier number NCT02121717). Previous studies, both in vitro and in vivo, demonstrated that CHI had moderate transcription activity in PPAR‐α, PPAR‐γ, and PPAR–δ types . It could upregulate the expression of genes like ANGPTL4 and PDK4 , which are involved in glucose and lipid metabolism.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…TZDs act as insulin sensitizers that improve glycemic control but have now become "Nonformulary oral options that are nonpreferred but can be considered in patients at high hypoglycemia risk where cost is an issue" because studies have linked these drugs to hepatotoxicity, increased risk for cardiovascular failure, myocardial infarction, increased risk for bladder cancer, and body weight gain [6,[25][26][27][28][29][30][31][32]. Despite the adverse effects of current medications, development of new PPAR agonists are still of great interest because of the unique and promising feature of this class of drug, including the ability to directly target insulin resistance and provide a more durable glycemic (HbA1c) control when compared to other antidiabetic medications [33]. In an attempt to reduce the reverse effects, alternative approaches were considered to target the PPAR receptors including partial PPARγ agonists [34][35][36][37][38][39][40][41][42][43][44], multitargeted cooperative PPARα/γ dual agonists [28,31,40,[45][46][47][48][49][50][51][52][53][54][55][56][57][58], and PPARα/β/γ pan-agonists [30,35,[59]…”
Section: Introductionmentioning
confidence: 99%